Sensory analysis tests for the development of infant cereal products in Venezuela (Publicaciones en Ciencias y Tecnología, 2019)
Sensory evaluation for the food industry is a key activity in the development of products that allows us to know the expectations and needs of consumers; therefore, applying sensory tests allows us to build a profile of a winning cereal in the market. This research presents an analysis of various sensory testing methods applied in the manufacturing of wheat-based infant cereals in Venezuela. A sample of twelve companies and a sensory panel of forty consumers were used. A comparative study was carried out between the discriminatory, affective and descriptive sensory tests; in addition to a correlation between the type of test used and consumer acceptance, using descriptive statistical analysis. Affective tests occupy 42% of application in companies nationwide, 32% use discriminatory tests and 26% correspond to descriptive tests. By correlating the test type and consumer acceptance, it was found that companies that use discriminatory, affective and descriptive tests obtain a product that meets consumer expectations, and as they stop applying these tests, the products are less attractive for the consumer.Keywords: Acceptability; formulation; wheat-based cereals; sensory testing.
Keywords: Acceptability; formulation; wheat-based cereals; sensory testing